Individual Plant-Soil Feedback Effects Influence Tree Growth and Rhizosphere Fungal Communities in a Temperate Forest Restoration Experiment - Lance, Andrew C.; Carrino-Kyker, Sarah R.; Burke, David J.; Burns, Jean H. (Frontiers in Ecology and Evolution, 2020)
Plant-soil feedbacks and the soil legacy effects that create them have important implications for community composition and restoration. However, relatively few field trials test the influence of soil legacy effectsplant-soil feedbacks, especially on longer-lived species, such as trees. Here we present a field restoration experiment with 10 ectomycorrhizal fungal tree species native to eastern North America. Trees were inoculated with soils collected from conspecifics in the field or from a heterospecific: Quercus rubra. Fagus grandifolia stem elongationFollowing 16 months of growth in the field, Carya ovata diameter increase was significantly increased greater in trees receiving the by heterospecific inoculant.tion following 16 months of growth in the field, and Tthis negative plant-soil feedback is consistent with its C. ovata’s natural co-occurrence with Q. rubra. Conversely, Quercus macrocarpa diameter increase and Carya cordiformis height increase were was significantly greater when inoculated with conspecific soils, and this positive plant-soil feedback is consistent with its their numerical dominance in natural communities. We found no evidence for phylogenetic Janzen-Connell effects or conservation of soil mutualists across tree species. We also quantified differences in soil fungal community structure with next generation sequencing methods (Illumina MiSeq) following 16 months in the field. Shannon’s diversity of fungal taxa was greater in heterospecific soils of seven of our nine experimental species, consistent with a diversifying influence of heterospecific Quercus rubra soil inocula. However, only one genus, Ulmus, exhibited differences in fungal community composition derived from conspecific and heterospecific sources, suggesting a stronger effect of focal tree species than of soil inocula source. The relatedness among focal tree species also influenced fungal community composition, with tree families and genera displaying different fungal communities. We suggest that future experiments should determine whether more diverse tree and fungal communities might have enhanced ecosystem functioning in tree restoration sites.